Considerations and statistics on 100 cases of pulmonary echinococcosis (E. P.) - Méndez Aserito, Hugo; Porras, Yamandú (Cirugía del Uruguay, 1973)
Statistics presented by the Surgery Service of the Mercedes Hospital comprise 100 cases of pulmonary hydatidosis over a 10-year period. 'he paper contains an analysis of therapy employed for each anatomo-clinical type, as well as basic surgical concepts common to all hydatid cysts of lung. Death-rate ( 1 % ) , morbility and complications with consequent reoperation are studied. These constitute a clear indication of the importance of this disease.